TAYLOR, Y. Inventory of documents - TAYLOR, Y. (ARCA, 2018)
Private papers of Y. Taylor, teacher [1945-1949]; clerk attorney's office [1950-1962]; clerk CSIR Library [1962-1966].
1938-1961; 3 Files; 0.44 metre
Keywords: TAYLOR, Y.; Reunited National Party; Voortrekker Century Festival; Republic Festival